2013
DOI: 10.1177/1933719113477486
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3 and Decay-Accelerating Factor Expression Levels Are Modulated by Human Chorionic Gonadotropin in Endometrial Compartments During the Implantation Window

Abstract: The control of complement activation in the embryo-maternal environment has been demonstrated to be critical for embryo survival. Complement proteins are expressed in the human endometrium; however, the modulation of this expression by embryo signals has not been explored. To assess the expression of complement proteins in response to human chorionic gonadotropin (hCG), we designed an experimental study using in vivo and in vitro models. Twelve fertile women were treated with hCG or left untreated during the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
(35 reference statements)
2
24
0
1
Order By: Relevance
“…One study has shown that hCG plays a role in this complement control, particularly on decay accelerating factor (DAF) and C3 protein, in in vitro and in vivo models (112).…”
Section: Immunological Actions Of Hcgmentioning
confidence: 99%
“…One study has shown that hCG plays a role in this complement control, particularly on decay accelerating factor (DAF) and C3 protein, in in vitro and in vivo models (112).…”
Section: Immunological Actions Of Hcgmentioning
confidence: 99%
“…57 C3 is localized in stromal and glandular compartments during secretory phase. 60 Consequently, hCG might function as an immune modulator responsible of the control of the complement system in the human endometrium. Overactivated complement C3 compromised fetal survival and led to fetal loss.…”
Section: Hcg and The Complement System In The Endometriummentioning
confidence: 99%
“…Moreover, decay-accelerating factor (DAF), one of complement regulatory proteins to protect host cells from the attack by the activated complement system, was increased in the luminal compartment, potentially to maintain a safe environment for embryonic implantation. 60 Consequently, hCG might function as an immune modulator responsible of the control of the complement system in the human endometrium. Recently, high dose (10 000 IU) of urine-purified hCG was shown to modulate uterine natural killer (uNK) cell proliferation via mannose receptors (CD206), rather than by the classical LH/hCG receptors which are not expressed on uNK cells.…”
Section: Hcg and The Complement System In The Endometriummentioning
confidence: 99%
“…Our study clearly correlated with other various studies done all over the world. [4][5][6][7][8][9][10][11] The intrauterine injection of hCG before the No. of embryo per transfer 2.9 ± 0.4 2.9 ± 0.5 embryo transfer is a simple procedure.…”
Section: Jsafog Discussionmentioning
confidence: 99%
“…9 It was reported that in several studies about the increase in C3 protein mRNA levels stromal cells in the endometrial biopsy culture of an infertile women during implantation window. 10 There is a definite positive correlation between beta-hCG concentration and implantation rates. 11 Studies are still being conducted in this field of interest.…”
Section: Introductionmentioning
confidence: 99%